A Bibliometric Analysis of the Surgical Safety Checklist: Trends, Impact and Future Directions - Cahyani, Kurnia Budi (Universitas Aisyah Pringsewu, 2023)
The Surgical Safety Checklist (SSC) is widely implemented tool aimed at improving patient safety and reducing surgical errors. This systematic review conduct a bibliometric analysis to provide insight into the trends, impact, and future directions of research related to the Surgical Safety Checklist.A systematic search of major scientific databases was conducted to identify relevant articles published within a specified timeframe. Keywords related to the Surgical Safety Checklist and bibliometric analysis were used to filter the articles. Inclusion criteria were applied to select the most relevant studies for analysis. The finding demonstrate the increasing global interest in topic.The bibliometric analysis a substantial growth in the number of publications related to the Surgical Safety Checklist over the years. The findings demonstrate the increasing global interest in this topic Key themes in research focus were discovered, including specific characteristics of checklist implementation, effectiveness, and associated consequences. The Analysis also highlighted the leading countries, institution, and authors contributing to the field.The systematic Review discusses the impact and implication of the research on the surgical safety checklist. It highlights the positive influence of the checklist in improving surgical outcomes and patient safety, improved safety culture in hospital. The review also explore emerging research directions, such as the integration of new technologies and the application of the checklist in different surgical specialties. Moreover, it identifies knowledge gaps and area that require further investigation to optimize checklist implementation an effectiveness.